SPEECH THERAPY MODEL BASED ON NEURO LINGUISTIC PROGRAMMING (NLP): OPTIMIZATION OF DEAF SPEECH ABILITY - Sakaria Sakaria; Asia M (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to describe the feasibility and effectiveness of a Neuro Linguistic Programming (NLP) based speech therapy model. The speech therapy model was developed using the Borg and Gall model at Makassar State SLB through the stages of research and information gathering, planning, development of initial product forms, and preliminary field trials. Data from expert validation results were analyzed using descriptive statistics, and data on the ability to speak with the deaf was analyzed using inferential statistical tests (t-test paired samples). The results of the study indicate that the developed speech therapy model is appropriate and effective for use in speech therapy for the deaf. The feasibility speech therapy model is used because it meets the feasibility aspects, namely the feasibility of supporting theory, the feasibility of orientation and goals, the feasibility of the reaction principle, the feasibility of therapeutic procedures, the feasibility of support systems, and the feasibility of implementing therapy. Speech therapy models based on Neuro Linguistic Programming (NLP) can improve the ability of the deaf to pronounce and understand the meaning of vocabulary and reduce anxiety when speaking.